STRATEGI MANAJEMEN PEMASARAN ISLAMI DALAM PENINGKATAN PENJUALAN PADA KEDAI SATE H.QADIR - Amir Amir; Wilda Al A'luf (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2023)
Marketing management strategy is a process capable of delivering organizations/companies to large market opportunities to increase sales and achieve the expected advantages. The marketing management strategy is also an important tool so that companies are able to win the competition. The purpose of marketing is to carry out transactions, serve, fulfill needs, and desires to satisfy consumers. While the marketing function is product development, if the products that have been circulating experience a decrease, to avoid this, it is necessary to add product functions according to business development. From the description of the problems that occur, the author focuses on two problem formulations, namely: 1) How is the marketing management strategy in increasing sales at Kedai Sate H.Qadir Denpasar Bali 2) What are the supporting and inhibiting factors of the marketing management strategy in increasing sales at Kedai Sate H.Qadir Denpasar Bali. The research method used is a qualitative research method with data collection techniques by means of observation, interviews, and documentation. The results obtained from this researcher are expected to provide a detailed and systematic explanation of Islamic marketing management strategies in increasing sales. The Islamic marketing management strategy carried out at Kedai Sate H. Qadir uses (marketing mix) called the 4Ps of product, price, promotion, place. The priority supporting factor is having a strategic place that is easily accessible to consumers and also communication aimed at attracting consumers who are outside the Denpasar Bali area. The inhibiting factor at Kedai Sate H. Qadir is that there are quite a lot of conditions in the Denpasar Bali area.